Seaweed Consumption Practices in Coastal Communities of Tawi-Tawi, Philippines - Albaris B. Tahiluddin; Fauzia R. Esmola; Suhana A. Abduraup; Aisa Mae B. Camsain; Wahaymin M. Jamil; Angelica B. Bermil; Romar A. Ujing; Adzlan D. Gunong; Samiya U. Damsik; Sitti Darmiya S. Baid; Fatima Qhurdee N. Hapid; Telmigi M. Mohammad; et al. (Phycology, 2025)
Seaweeds represent a vital yet often understudied component of the diet and cultural heritage of many coastal communities globally. This study investigated seaweed consumption practices in coastal communities of Tawi-Tawi, Philippines, through one-to-one interviews (n = 280) and focus group discussions (n = 7). The study revealed that nearly all (99%) of the population consumes seaweeds, with women comprising the majority of consumers who have done so since childhood (68% female vs. 32% male). These consumers were predominantly married (79%), within the 21–40 age group (53%), with families of 5–7 members (43%), practicing Islam (97%), and belonging to the Sama tribe (71%). A significant portion (48%) had resided in the area for 21–30 years, attained elementary to high school education (66%), and had a monthly income ranging from 1000 to 10,000 Philippine pesos (72%). Seaweed consumption was a family-wide practice (88%), including children, who typically started around 4–8 years old (61%), driven by perceived nutritional benefits (43%), preferred flavor (80%), affordability (19%), ease of preparation (33%), and cultural integration (23%). The primary edible seaweeds identified were Kappaphycus alvarezii (63%), K. striatus (58%), Kappaphycus spp. (47%), Eucheuma denticulatum (57%), Caulerpa lentillifera (64%), Caulerpa spp. (51%), C. cf. macrodisca ecad corynephora (45%), C. racemosa (30%), and Solieria robusta (49%), with less frequent consumption of K. malesianus (8%), Chaetomorpha crassa (3%), Gracilaria spp. (0.72%), and Hydroclathrus clathratus (0.36%). Specific plant parts were preferred for certain species, and preparation predominantly involved raw (75%) or cooked (77%) salads with spices, primarily prepared by mothers (72%). Consumers generally avoided seaweeds showing signs of ice-ice disease (95%), pale coloration (91%), or epiphyte infestation (84%). Consumption frequency was typically 1–3 times per week (45%), with knowledge largely passed down through generations (95%). Seaweed salads were primarily consumed as a viand (92%) at home (97%), with locals perceiving seaweed consumption as contributing to a healthy diet (40%) and overall well-being [e.g., aiding hunger (76%), improving digestion (20%), preventing obesity (14%), and aiding brain development (3%)]. The study’s findings emphasize the significant yet often overlooked role of seaweeds in the food systems and cultural heritage of Tawi-Tawi’s coastal communities. Future efforts should prioritize the sustainable management of wild resources, explore the cultivation of diverse edible species, and enhance nutritional awareness. Further research into traditional seaweed knowledge holds broader value.